Novel extruded palm tree wood-derived activated carbon-based SrTiO3 for wastewater treatment in continuous system: evaluation of synthesis condition, LHSV, and pH - Ghandour, Raymond; Ali, Ali B. M.; Kadhum, Abdul Amir H.; Diab, M. A.; El-Sabban, Heba A.; Shah, Mumtaj; Nagar, Harsha (Inorganic Chemistry Communications, 2025)
SrTiO3 is a potential photocatalyst, while its wide band gap hinders sufficient adsorption of visible light and decreases the photocatalytic efficiency. Herein, activated carbon (AC) derived from palm tree wood was functionalized with varying weight percentages (10, 20, and 30 wt%) of SrTiO3 nanoparticles and evaluated for its efficiency in the photodegradation of Cefixime (CFX) in a continuous system. The effects of activation temperature on the morphological properties of AC, along with operational parameters such as Liquid Hourly Space Velocity (LHSV) (3, 4, and 5 h- 1) and the pH of the initial CFX solution (4, 6.5, and 9), were examined to optimize the photocatalytic performance. The photocatalyst activated at 900 degrees C with 30 wt% SrTiO3 exhibited the highest activity, and were characterized by XRD, BET, FE-SEM, and UV-Vis analyses. Optimal conditions for CFX degradation were found at pH of 6.5 and LHSV of 5 h- 1. Additionally, hydroxyl (center dot OH) and superoxide (center dot O2-) radicals were identified as key species in CFX photodegradation process. Hence, these findings contribute to the design and development of highly-active continuous photocatalytic system.
Keywords: antibiotic; Continuous Photocatalytic Degradation; environmental remediation; Risk Management; Wastewater treatment